Emerging climate impact on carbon sinks in a consolidated carbon budget - Pierre Friedlingstein; Corinne Le Quéré; Michael O’Sullivan; Judith Hauck; Peter Landschützer; Ingrid T. Luijkx; Hongmei Li; Auke van der Woude; Clemens Schwingshackl; Julia Pongratz; Pierre Regnier; Robbie M. Andrew; et al. (Nature, 2026)
Abstract Despite the adoption of the Paris Agreement 10 years ago, carbon dioxide (CO 2 ) emissions from burning fossil fuels continue to increase, pushing atmospheric CO 2 levels to 423 ppm in 2024 and driving human-induced warming to 1.36 °C, within years of breaching the 1.5 °C limit 1,2 . Accurate reporting of anthropogenic and natural CO 2 sources and sinks is a prerequisite to tracking the effectiveness of climate policy and detecting carbon-sink responses to climate change. Yet notable mismatches between reported emissions and sinks have so far prevented confident interpretation of their trends and drivers 1 . Here we present and integrate recent advances in observations and process understanding to address some long-standing issues in global carbon budget estimates. We show that the magnitude of the natural land sink is substantially smaller than previously estimated, whereas net emissions from anthropogenic land-use change are revised upwards 1 . The ocean sink is 15% larger than the land sink, consistent with recent evidence from oceanic and atmospheric observations 3,4 . Climate change reduces the efficiency of the sinks, particularly on land, contributing 8.3 ± 1.4 ppm to the atmospheric CO 2 increase since 1960. The combined effects of climate change and deforestation have turned Southeast Asian and large parts of South American tropical forests from CO 2 sinks to sources. This underscores the need to halt deforestation and limit warming to prevent further loss of carbon stored on land. Improved confidence in assessments of CO 2 sources and sinks is fundamental for effective climate policy.